The guild book of the barbers and surgeons of York (British Library, Egerton MS 2572) study and edition - Wragg, Richard D. (York Medieval Press, 2021)
A new exploration of the secular manuscripts and medieval medical texts associated with the York Guild and its members.
Keywords: Guild Book of the Barber Surgeons of York.